2022
DOI: 10.3390/cancers14184435
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SSTR PET on Inter-Observer Variability of Target Delineation of Meningioma and the Possibility of Using Threshold-Based Segmentations in Radiation Oncology

Abstract: Aim: The aim of this study was to assess the effects of including somatostatin receptor agonist (SSTR) PET imaging in meningioma radiotherapy planning by means of changes in inter-observer variability (IOV). Further, the possibility of using threshold-based delineation approaches for semiautomatic tumor volume definition was assessed. Patients and Methods: Sixteen patients with meningioma undergoing fractionated radiotherapy were delineated by five radiation oncologists. IOV was calculated by comparing each de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
(30 reference statements)
0
0
1
Order By: Relevance
“…The manufacturer supplied automatic set threshold of 42% of SUVmax proved adequate for tumor volume determination and MTV which is contradictory to the findings described by Kriwanek et al (Kriwanek et al 2022 ) examining the inter-observer variability of target delineation of meningioma were a threshold of 14% of SUVmax was deemed adequate. In the same study, a general increase in delineated tumor volume was present for most physicians, although a major drop was seen in one physician.…”
Section: Discussioncontrasting
confidence: 65%
“…The manufacturer supplied automatic set threshold of 42% of SUVmax proved adequate for tumor volume determination and MTV which is contradictory to the findings described by Kriwanek et al (Kriwanek et al 2022 ) examining the inter-observer variability of target delineation of meningioma were a threshold of 14% of SUVmax was deemed adequate. In the same study, a general increase in delineated tumor volume was present for most physicians, although a major drop was seen in one physician.…”
Section: Discussioncontrasting
confidence: 65%
“…The results for the meningioma cohort within the present study are in concordance with the current literature in terms of better agreement between observers, resulting in more consensual delineation and accurate target definition when integrating PET/CT into standard CT and MR. This finding underlines the importance of integrating PET/CT into target definition for skull base meningioma radiotherapy planning [13][14][15].…”
Section: Discussionmentioning
confidence: 59%
“…A recent study suggested a 1.7 fold meninges SUV peak as threshold for semiautomatic delineation of tumor volume [59]. SSTR PET-based tumor volume definition for radiotherapy planning has been investigated in few retrospective and small studies which indicated potentially increased accuracy and decreased interobserver variability compared to MRI [13,62]. Overall, further studies are warranted to assess the optimal method for standardized tumor segmentation and threshold definitions.…”
Section: Cut-off Thresholds For Definition Of Biological Tumor Volumementioning
confidence: 99%